Group versus individual format of intervention for aggressive children: Moderators and predictors of outcomes through 4 years after intervention. (December 2019) - Lochman, John E.; Glenn, Andrea L.; Powell, Nicole P.; Boxmeyer, Caroline L.; Bui, Chuong; Kassing, Francesca; Qu, Lixin; Romerro, Devon E.; Dishion, Thomas
Abstract: This study originated in collaboration with Thomas Dishion because of concerns that a group format for aggressive children might dampen the effects of cognitive-behavioral intervention. Three hundred sixty aggressive preadolescent children were screened through teacher and parent ratings. Schools were randomized to receive either an individual or a group format of the child component of the same evidence-based program. The results indicate that there is variability in how group-based cognitive-behavioral intervention can affect aggressive children through a long 4-year follow-up after the end of the intervention. Aggressive children who have higher skin conductance reactivity (potentially an indicator of poorer emotion regulation) and who have a variant of the oxytocin receptor gene that may be associated with being hyperinvolved in social bonding have better outcomes in their teacher-rated externalizing behavior outcomes over time if they were seen individually rather than in groups. Analyses also indicated that higher levels of the group leaders' clinical skills predicted reduced externalizing behavior problems. Implications for group versus individual format of cognitive-behavioral interventions for aggressive children, and for intensive training for group therapists, informed by these results, are discussed.